The Effect of Financial Distress on Earnings Management with Managerial Ownership as Moderating Variable - Natha, I Komang Sutrisna Adi; Wirajaya, I Gde Ary (E-Jurnal Akuntansi, 2024)
This study sought to gather empirical evidence about the effect of financial distress on earnings management moderated by managerial. The study conducted on transportation and logistics firms listed on the IDX during the period from 2020 to 2022. The sample determining method used nonprobability sampling through total sampling with 60 observations as sample. Moderated Regression Analysis (MRA) was utilized as the data analysis technique. The result showed that manager would take advantage of asymmetric information and were encouraged to take earnings management actions in order to minimize the impact of financial distress. Furthermore, managerial ownership weakened the influence of financial distress on earnings management. When faced with conditions of financial distress, management owned the firm shares would act in harmony with principal.